METHODOLOGY OF ASSESSMENT OF THE BRANDING STRATEGY (Development Service Industry Management, 2025)
The aim of the article is to substantiate methodological approaches to brand evaluation in the context of defining a brand as a marketing asset in the capitalization of an enterprise.The study used economic and statistical research methods in analyzing practical experience in using brand evaluation methods; theoretical and methodological approaches in analyzing the use of brand evaluation methods; grouping and classification - in determining the most common approaches in brand evaluation. The distinctive features of brand leadership compared to classical brand management are identified. The role of brand valuation as an intangible asset in the structure of an enterprise's assets is substantiated. It was substantiated the three most common methodological approaches to brand valuation: cost, comparative and profit. The problems of the practice of recognition, assessment, protection, and revaluation of intangible assets and brands in Ukraine are formulated in comparison with foreign practices in this area. One of the serious problems is the lack of harmonization of terminology in the field of brand valuation, as an intangible asset, with international valuation standards. The practical significance of the research is analysis showed that in world practice it is accepted to use the profit approach to brand valuation, in which the value is determined based on the discounted value of cash flows. Applied aspects of the application of this method of brand valuation are presented. Based on the above-mentioned brand valuation methods, a number of methods were proposed that allow taking into account the shortcomings of generally accepted approaches. The scientific novelty of the following brand valuation methods are proposed, which can be implemented in the practice of assessing local and global brands: a method of assessing the value of brands using points; a method of calculating the book value of a brand and its replacement cost; a method of assessing the value of a brand using market transactions; a model of brand value indices. Further research is aimed at developing a methodology for evaluating brands in the digital economy, taking into account new influencing factors.
Keywords: brand assessment methods; rand; brand value index; evaluation